Do Work Motivation Have Roles in Employee Performance? Insight from Kampung Marketer Social Entrepreneuship - Nurdian Susilowati; Angga Pandu Wijaya; Susmy Lianingsih (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2021)
The exploration of employee performance in social entrepreneurship has gained increasing relevance among researchers, particularly in rural economic. Previous research has not explored much of the role of work motivation in strengthening job training and work incentives on employee performance. This study aims to determine the effect of job training and work incentives on employee performance and elaborate on work motivation as a moderating variable. This research respondents were all employees working in Kampung Marketer with a total sample of 161 people. Data collected by distributing questionnaires to respondents. Data analysis technique employs moderated analysis regression, preceded by a validity test, a reliability test and a classic assumption test. The results showed that job training has a positive and significant effect on the employee performance of employees. Work incentives have an insignificant impact on the performance of employees. Motivation can reduce the effect of job training and enervate work incentive toward employee performance. Research results represent that work incentives essential to generate employee performance; otherwise, higher motivation can emerge negatively and influence employee performance. The research is beneficial to manage human resource and deliver cutting-edge insight in managing employee.